Correlation between Disability and Basic Movement Ability in Elderly People - Xiangtian WEN, Wenyi NIU (Zhongguo quanke yixue, 2022)
Background As the pace of population aging accelerates, the estimated people aged≥65 years will account for more than 20% of the total population in China by 2030, among them those with disability will expand to 77 million, possessing more than 57% of the total disability population. Decline in the basic movement ability can lead to reduced quality of life, and increased burden on society and families. Objective To explore the correlation of basic movement ability with disability status in the elderly. Methods The study was carried out in March 2021. Data were collected from the database of China Health and Retirement Longitudinal Study (CHARLS) in 2015, involving 5 276 surveyees aged≥60 years with complete values of assessed basic movement ability and disability and key variables (gender, age, household location, education level) . The grip strength test, five-repetition sit-to-stand (FRSTS) test, standing balance test and gait speed test were used to evaluate the basic movement ability. Disability prevalence was evaluated by the Instrumental Activities of Daily Living (IADL) Scale. The grip strength level, gait speed, and prevalence of completion of standing balance test and FRSTS test were compared by the prevalence of disability. Logistic regression was used to analyze the correlation of basic movement ability and disability status. Results The average grip strength value for all individuals was 27.92 (9.02) kg. The prevalence of poor, fair and good grip strength was 32.47% (1 713/5 276) , 33.55% (1 770/5 276) , and 33.98% (1 793/5 276) , respectively. 3 930 cases (74.49%) completed the standing balance test. 5 128 cases (97.19%) completed the FRSTS test. The average gait speed was 0.96 (3.12) m/s for all elderly persons. The prevalence of slow, moderate and fast gait speed was 33.17% (1 750/5 276) , 33.34% (1 759/5 276) , and 33.49% (1 767/5 276) , respectively. 1 419 cases (26.90%) were assessed with disabilities. The prevalence of disability varied significantly by grip strength, standing balance and FRSTS test performance, and gait speed (P<0.05) . Logistic regression results showed that, poor grip strength, inability to complete the standing balance test and the FRSTS test, and low gait speed were associated with increased risk of disability in both 60-74 years and ≥75 years age groups (P<0.05) . The inability to complete the FRSTS test was associated with 3.045 times higher risk of disability in the 60-74 age group, and 4.126 times higher risk of disability in the≥75 age group (P<0.05) . Conclusion The elderly with poor basic movement ability are prone to disability. In view of this, it is recommended to take measures to improve the basic movement ability of the elderly to delay the onset of disability or relieve the level of disability, thereby improving the quality of life and reducing the health care needs of them, and alleviating the caregiving burden of their family caregivers.